Status and Strategy for Human Resource Development of Healthcare Sector in Soc Trang Province (Vietnam) - Nguyen Hong Nga (Journal of Global Pharma Technology, 2018)
The basic motivation promotes economic growth and promotes industrialization and modernization of the country, which is human factors, is the human resource of training and comprehensive development. The human being is motivated, as the target of development, is the factor that decides every victory. The total medical manpower of the province now has not yet responded to the prevention and examination, healing for the people, missing many postgraduate officers, especially majors in the field of treatment so the quality of the examination, healing throughout the system is gaining effectiveness yet high. Because of the lack of doctors at all times, the quality of examination and treatment for the people has many limitations, especially in medical terms, and is causing overload in treatment facilities in the province. In Soc Trang province (Vietnam), there have been a number of projects investing in the construction of private polyclinics that have been invested in construction and start. On the basis of the difficulties and obstacles mentioned above, to develop a human resource that meets the requirement of disease examination and prevention for the people. As a result, the study evaluated the status of healthcare officers in the period of 2013-2017 and building the orientation of the human resource development in Soc Trang province (Vietnam) to the year 2025 is essential.Keywords: Healthcare, Orientation, Human resource, Development, Soc Trang, Vietnam.